Mergers and acquisitions research — A bibliometric analysis. Issue 6 (December 2022) - Eulerich, Marc; Kopp, Raphael; Fligge, Benjamin
Abstract: Mergers and acquisitions (M&A) remain a popular vehicle for organizational development to ensure future competitiveness. However, despite the extensive body of research in recent decades, significant gaps can be observed between the understanding of the phenomenon M&A in the literature and the importance of M&A activities in practice. Heterogeneous perspectives from different schools of thought, contradictory findings and controversies, and changing economic environments make M&A research a complex endeavor and highlight the need for integrative approaches and holistic perspectives. This paper takes a holistic view of M&A research to map interrelationships among key documents, authors, institutions, and countries; trace the evolution of M&A research over time; and suggest avenues for future research to expand the boundaries of M&A scholarship. For this purpose, a sample of 580 articles from 9 leading management science journals was examined bibliometrically, including 42, 630 citations and 18, 734 unique references for the years 1963–2019.